Corticosteroid receptor immunoreactivity in neurons of the hippocampus, amygdala and paraventricular nucleus, in rats under maternal separation and chronic stress: Effects of tianeptine - Trujillo, Verónica (2014)
Fil: Trujillo, Verónica. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.